Cover Picture: Molecular Property Optimizations with Boundary Conditions through the Best First Search Scheme (ChemPhysChem 10/2016). Issue 10 (4th May 2016) - De Vleeschouwer, Freija; Geerlings, Paul; De Proft, Frank
Abstract : The Front Cover picture shows how information gathered from single‐property optimizations can be exploited to effectively, efficiently, and rationally design novel compounds with multiple desired properties, especially when constraints are applicable. More information can be found in the Concept by F. De Vleeschouwer et al. onpage 1414 in Issue 10, 2016 (DOI:10.1002/cphc.201501189 ).